Genetic and morphological characterization of Trichuris myocastoris found in Myocastor coypus in the Czech Republic - Rylková, K; Tůmová, E; Brožová, A; Jankovská, I; Vadlejch, J; Čadková, Z; Frýdlová, J; Peřinková, P; Langrová, I; Chodová, D; Nechybová, S; Scháňková, Š (Parasitology research, 2015)
Trichuris sp. individuals were collected from Myocastor coypus from fancy breeder farms in the Czech Republic. Using morphological and biometrical methods, 30 female and 30 male nematodes were identified as Trichuris myocastoris. This paper presents the first molecular description of this species. The ribosomal DNA (rDNA) region, consisting of internal transcribed spacer (ITS)-1, 5.8 gene and ITS-2, was sequenced. Based on an analysis of 651 bp, T. myocastoris was found to be different from any other Trichuris species for which published sequencing of the ITS region is available. The phylogenetic relationships were estimated using the maximum parsimony methods and Bayesian analyses. T. myocastoris was found to be significantly closely related to Trichuris of rodents than those of ruminants.
Keywords: DNA, Ribosomal Spacer; rDNA; ITS1-5.8S-ITS2; Bayes Theorem; Trichuris; trichurióza; Česká republika; Myocastor coypus; Parasites; mužské pohlaví; DNA, Helminth; DNA, Ribosomal; Czech Republic; Bayesova věta; Trichuris myocastoris; Base Sequence; sekvence nukleotidů; ženské pohlaví; zvířata; Humans; DNA helmintů; fylogeneze; ribozomální DNA; Trichuriasis; Female; Phylogeny; mezerníky ribozomální DNA; lidé; Male; Animals